Isomer-dependent fragmentation dynamics of inner-shell photoionized difluoroiodobenzene. Issue 21 (19th May 2017) - Ablikim, Utuq; Bomme, Cédric; Savelyev, Evgeny; Xiong, Hui; Kushawaha, Rajesh; Boll, Rebecca; Amini, Kasra; Osipov, Timur; Kilcoyne, David; Rudenko, Artem; Berrah, Nora; Rolles, Daniel
Abstract : The fragmentation dynamics of 2, 6- and 3, 5-difluoroiodobenzene after iodine 4d inner-shell photoionization with soft X-rays are studied using coincident electron and ion momentum imaging. Abstract : The fragmentation dynamics of 2, 6- and 3, 5-difluoroiodobenzene after iodine 4d inner-shell photoionization with soft X-rays are studied using coincident electron and ion momentum imaging. By analyzing the momentum correlation between iodine and fluorine cations in three-fold ion coincidence events, we can distinguish the two isomers experimentally. Classical Coulomb explosion simulations are in overall agreement with the experimentally determined fragment ion kinetic energies and momentum correlations and point toward different fragmentation mechanisms and time scales. While most three-body fragmentation channels show clear evidence for sequential fragmentation on a time scale larger than the rotational period of the fragments, the breakup into iodine and fluorine cations and a third charged co-fragment appears to occur within several hundred femtoseconds.